Question 29

loading...

Prev/Next links

Jambmaths question: 

Simplify $3\tfrac{1}{2}-(2\tfrac{1}{3}\times 1\tfrac{1}{4})+\tfrac{3}{5}$

Option A: 

$1\tfrac{11}{60}$

Option B: 

$1\tfrac{1}{60}$

Option C: 

$2\tfrac{11}{60}$

Option D: 

$2\tfrac{1}{60}$

Jamb Maths Solution: 

$\begin{align}  & 3\tfrac{1}{2}-(2\tfrac{1}{3}\times 1\tfrac{1}{4})+\tfrac{3}{5}=\tfrac{7}{2}-(\tfrac{7}{3}\times \tfrac{5}{4})+\tfrac{3}{5} \\ & =\tfrac{7}{2}-\tfrac{35}{12}+\tfrac{3}{5} \\ & =\tfrac{210-175+36}{60}=\tfrac{71}{60}=1\tfrac{11}{60} \end{align}$

Jamb Maths Topic: 
Year of Exam: